THE EFFECTS OF DIGITAL CURRENCY (ENAIRA) ADOPTION ON NIGERIA ECONOMY - Adegbite, T. A.; Aremu, M. A. (Farabi Journal of Social Sciences, 2022)
This study examined the determinants of eNaira adoption in Nigeria, also examined the effects of eNaira adoption on economy in Nigeria. The utilized data were randomly collected from banks staff, economists, and Nigerians through questionnaires. These were rigorously analyzed through MANOVA, correlation, chi-square and Crombach’s Alpha statistics reliability. It is concluded that eNaira will have positive significant effect on economy in Nigeria in terms of employment generation, economic stability, easy facilitation of transaction, security of money, direct welfare disbursements enablement, Revenue and tax collection Increment, cost of processing cash reduction, resilient payment system supports, Central Bank currency usability improvement, and economic activities enhancement. It will also serve as medium of exchange, secured store of value, and stable unit of account. It is recommended that CBDC should establish validation scheme (centralized or decentralized) to prevent double spending or identity theft of eNaira code. Also, there is need to educate people about the eNaira by the government on the importance of this new development. Citizens must enlightened to understand the difference between cash deposits’ digital representation in bank accounts and eNaira in digital wallets. There must also be a programme which should be organized by CBN to deepen the enlightenment of eNaira in the country. Keywords: eNaira; economy; adoption; education: blockchain: government policy.